Natural mechanical degradation measurements in slow speed bearings - Elforjani, Mohamed; Mba, David (Elsevier Science B.V., Amsterdam., 2009)
Acoustic emission (AE) technology applied to condition monitoring is gaining acceptance as a useful complimentary tool. This paper demonstrates the use of AE measurements to detect, monitor the growth and locate natural defect initiation and propagation in a conventional rolling element bearing. To undertake this task a special purpose test-rig was built to allow for accelerated natural degradation of a bearing race. It is concluded that crack initiation and its subsequent propagation is detectable with AE technology. The paper also investigates the source characterisation of E signals associated with a defective bearing whilst in operation.
Keywords: Acoustic emission Condition monitoring Natural degradation Thrust bearings rolling element bearings acoustic-emission